2023
DOI: 10.3390/molecules28062442
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Bioactivity Evaluation of Novel 2-(pyrazol-4-yl)-1,3,4-oxadiazoles Containing an Imidazole Fragment as Antibacterial Agents

Abstract: Imidazole alkaloids, a common class of five-membered aromatic heterocyclic compounds, exist widely in plants, animals and marine organisms. Because of imidazole’s extensive and excellent biological and pharmacological activities, it has always been a topic of major interest for researchers and has been widely used as an active moiety in search of bioactive molecules. To find more efficient antibacterial compounds, a series of novel imidazole-fragment-decorated 2-(pyrazol-4-yl)-1,3,4-oxadiazoles were designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…5 ), most of which are essential in increasing the resistance to insects and diseases in plants [ 18 29 ]. Except for the GTE10 and FLS2 genes, almost all of these genes are relevant to the metabolism of alkaloids, a kind of antibacterial compounds [ 50 , 51 ], which suggest that alkaloids may be an effective external admixture for the defense against agave purple curl leaf disease. The results of qPCR analysis found that the AsRCOM gene may be the most crucial gene among all the hub genes identified by WGCNA analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5 ), most of which are essential in increasing the resistance to insects and diseases in plants [ 18 29 ]. Except for the GTE10 and FLS2 genes, almost all of these genes are relevant to the metabolism of alkaloids, a kind of antibacterial compounds [ 50 , 51 ], which suggest that alkaloids may be an effective external admixture for the defense against agave purple curl leaf disease. The results of qPCR analysis found that the AsRCOM gene may be the most crucial gene among all the hub genes identified by WGCNA analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%